(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
During the preparation of aqueous suspension of whiskers of cellulose by sulfuric acid hydrolysis some hydroxyl groups on the surface were sulfated. In order to determine the degree of sulfatation we have used the acid-basic and conductometric titration methods. It has been shown that these methods allow to determine the degree of sulfatation and the percent content of sulfur in the dry cellulose.